PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT (TGT) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA PADA MATERI SEGI EMPAT DI KELAS VII A SMPN 3 PARINGIN - Meina Noriyana (Universitas Lambung Mangkurat, 2013)
It has conducted research about the implementation of cooperative learning model with team game tournament (TGT) type on Rectangular material. The purpose of this study was to determine students learning activity and enhancing mathematics learning outcomes through cooperative learning model with TGT type. This research was conducted in two cycles with three meetings. The subjects were students of class VII A 3 Paringin SMP consisting of 15 students. The study states that the cooperative learning model with TGT type could (1 )increase students activity with excellent category (2) improving student learning outcomes from the first to the second cycle thoroughness iondividual of 9 students to 13 students and classical completeness of 60 % to 87%. This means that the cooperative learning of TGT type can improve students activity and aktivas and learning outcomes.Key words: team game tournament, activities and learning outcomes, rectangular.